Analisis Kesantunan pada Penggunaan Campur Kode oleh Mahasiswa Prodi Pendidikan Bahasa Jepang (Kajian Pragmatik) - Pramesti, Putu Dewi Merlyna Yuda; Hermawan, Gede Satya (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 6 No 1 (2024)DO - 10.24843/JS.2024.v06.i01.p04, 2024)
Politeness is essential in interaction to avoid conflict between the speaker and the hearer. This article describes politeness by students and lecturers in academic interaction at the Japanese Program in Undiksha. This study is qualitatively approached using pragmatics design. The data were collected using the technique of observation by listening, writing notes, and participating.  The data was then, analyzed using an interactive model from Miles & Huberman. The data were classi?ed according to the face theory of Brown & Levinson i.e. strategy of positive politeness and ?rategy of negative politeness. Data analysis reveals positive politeness strategies and negative politeness strategies students use in academic interaction at the Japanese Program in Undiksha. Both methods contained a constituent such as code-mixing. The reason for using code mixing in speech between lecturer and students is not only from speech situation but most part because of politeness factor. Using code-mixing of the Indonesian language and Japanese, made the speaker comfortable speaking because the code-mixing can make the utterance still in polite mode and formal form.